2021
DOI: 10.3389/fgene.2021.665469
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk Genes of Autism Spectrum Disorders

Abstract: Autism spectrum disorder (ASD) refers to a wide spectrum of neurodevelopmental disorders that emerge during infancy and continue throughout a lifespan. Although substantial efforts have been made to develop therapeutic approaches, core symptoms persist lifelong in ASD patients. Identifying the brain temporospatial regions where the risk genes are expressed in ASD patients may help to improve the therapeutic strategies. Accordingly, this work aims to predict the risk genes of ASD and identify the temporospatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…12, indicates that high specificity refers to a lower error rate. (12) specificity = number of TN number of TN + number of FP Fig. 6 The performance of different classifiers evaluated on SFARI dataset using different semantic similarity measures in terms of precision Fig.…”
Section: Performance Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…12, indicates that high specificity refers to a lower error rate. (12) specificity = number of TN number of TN + number of FP Fig. 6 The performance of different classifiers evaluated on SFARI dataset using different semantic similarity measures in terms of precision Fig.…”
Section: Performance Measuresmentioning
confidence: 99%
“…A support vector machine model was built in [ 12 ] to identify ASD risk genes and their influence on the temporospatial areas in the brain at different times using gene expression. Some researchers utilized deep learning techniques in gene prediction models [ 13 ], the DeepHE model was proposed to train a multilayer network using DNA sequence data and the data from the protein-to-protein network (PPI).…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of this approach is the significant clinical and biological heterogeneity of subjects with ASD [ 69 , 70 ]. Molecular genetics studies have identified a few hundred ASD risk genes [ 71 , 72 ] that may significantly amplify the difficulties in identifying reliable biomarkers for the disorder. ASD susceptibility genes, however, appear to converge in a discrete number of biological pathways [ 72 ]: several lines of evidence suggest that many of these biological pathways (and thus many genes) are shared, at least in children and adolescents, among different psychiatric disorders [ 73 , 74 , 75 , 76 ].…”
Section: Conclusion and Limitations Of The Studymentioning
confidence: 99%
“…In the largest study to date, researchers analysed multiple generations from over two million families located in Denmark, Finland, Sweden, Israel, and Western Australia, and found the occurrence of ASD could mainly be attributed to genetic factors, that is about 80% of the time (Bai et al, 2019). There are currently no definitive genetic markers identified, but the online human gene database, GeneCards, lists 7,211 genes potentially related to ASD (GeneCards, 2021;Lin et al, 2021). The most frequent mutation associated with the neuropathology of ASD involves a mutation in the SHANK3 protein that encodes for signalling molecules present in postsynaptic receptors (Jaramillo et al, 2020).…”
Section: Aetiologymentioning
confidence: 99%
“…The most frequent mutation associated with the neuropathology of ASD involves a mutation in the SHANK3 protein that encodes for signalling molecules present in postsynaptic receptors (Jaramillo et al, 2020). A mutation of this protein inhibits proper signalling between neurons, leading to atypical structural development and functioning of neurons (Amaral, 2017;Lin et al, 2021;Lutz et al, 2020).…”
Section: Aetiologymentioning
confidence: 99%